2012
DOI: 10.1097/pcc.0b013e31822f173c
|View full text |Cite
|
Sign up to set email alerts
|

Washing red blood cells and platelets transfused in cardiac surgery reduces postoperative inflammation and number of transfusions

Abstract: Objective Children undergoing cardiac surgery with cardiopulmonary bypass (CPB) are susceptible to additional inflammatory and immunogenic insults from blood transfusions. We hypothesize that washing red blood cells (RBC) and platelets transfused to these patients will reduce post-operative transfusion-related immune modulation and inflammation. Design Prospective randomized controlled clinical trial. Setting University hospital pediatric cardiac intensive care unit. Patients Children from birth to 17 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 66 publications
4
106
2
Order By: Relevance
“…In addition, adverse clinical outcomes were more common especially in critically ill patients [11-13]. A study by Cholette et al found that transfusion of washed RBCs and platelets during cardiac surgery reduced postoperative inflammation and number of transfusions [14]. However, several recent large prospective randomized-controlled trials (RCTs) have examined the harmful effects of transfusing long-term stored RBCs, and found no statistical significant difference in the in-hospital mortality among a general population of hospitalized patients [15], frequency of 5 major adverse outcomes among premature low-birth-weight infants [16], 90-day mortality among critical care patients [17] and Multiple Organ Dysfunction Score following cardiac surgery [18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, adverse clinical outcomes were more common especially in critically ill patients [11-13]. A study by Cholette et al found that transfusion of washed RBCs and platelets during cardiac surgery reduced postoperative inflammation and number of transfusions [14]. However, several recent large prospective randomized-controlled trials (RCTs) have examined the harmful effects of transfusing long-term stored RBCs, and found no statistical significant difference in the in-hospital mortality among a general population of hospitalized patients [15], frequency of 5 major adverse outcomes among premature low-birth-weight infants [16], 90-day mortality among critical care patients [17] and Multiple Organ Dysfunction Score following cardiac surgery [18].…”
Section: Introductionmentioning
confidence: 99%
“…Seven (of 15) patients in the thrombosis group and 13 (of 24) patients in the non-thrombosis group received washed red cells as per their original study assignment [9] ( Table 1). The thrombosis group had significantly more central shunt procedures and tetralogy of Fallot repairs compared to the non-thrombosis group, otherwise surgeries for underlying congenital cardiac diseases did not differ significantly.…”
Section: Resultsmentioning
confidence: 99%
“…All patients were previously enrolled in a randomized trial of washed blood transfusions as previously reported [9]. The protocol was approved by the URMC Research Subjects Review board.…”
Section: Methodsmentioning
confidence: 99%
“…47 However, a RCT of red cell washing in paediatric cardiac surgery patients failed to show a clinical benefit, although there was a reduction in a measure of inflammation (IL-6 : IL-10 ratio). 46 Importantly, no adverse effects of this technique were reported in recipients. Standard cell saver devices use low-speed centrifugation with resuspension in normalised saline without apparent detriment to human autologous or allogenic red cells.…”
Section: Red Cell Washingmentioning
confidence: 99%